Sea-Air Exchange of Methane in Shallow Inshore Areas of the Baltic Sea - Lundevall-Zara, Maysoon; Lundevall-Zara, Erik; Brüchert, Volker (Frontiers in Marine Science, 2021)
We report sea-air fluxes of methane in physically and biologically distinct inshore habitats of the Baltic Sea with the goal to establish empirical relationships that allow upscaling of local site-specific flux measurements. Flux measurements were conducted using floating chambers with and without bubble shields, and by using a boundary layer gas transfer model before, during, and after an annually occurring algal bloom from June to October 2019. Water and air temperature, salinity, wind, sediment organic content, and organic content of floating algal biomass were found to successfully discriminate the different habitats in terms of methane flux, both over periods of days and over a season. Multivariate statistical analysis was used to establish the relative environmental forcing of methane emissions over one growth season for each flux method. Floating algal biomass carbon and sediment organic content were identified as the most important controlling factors for methane emissions based on flux chamber measurements over a period of days to weeks, whereas wind velocity was the most important factor based on the gas transfer model on these time scales. Over the season, water and air temperature were the most important controlling factors with both methods. We present a first attempt how our observations can be extrapolated to determine the coastal methane emission along the coastline.